Tuning the nuclearity of [Mo2O2S2]2+-based assemblies by playing with the degree of flexibility of bis-thiosemicarbazone ligands. Issue 10 (13th February 2023) - Cebotari, Diana; Calancea, Sergiu; Marrot, Jerôme; Guillot, Régis; Falaise, Clément; Guérineau, Vincent; Touboul, David; Haouas, Mohamed; Gulea, Aurelian; Floquet, Sébastien
Abstract : Two families of binuclear or tetranuclear [Mo V 2 O2 S2 ] 2+ -based thiosemicarbazone complexes are obtained by varying the rigidity/flexibility of bis-thiosemicarbazone ligands. Abstract : [MoV2O2 S2 ] 2+ -based thiosemicarbazone complexes appear as very promising molecules for biological applications due to the intrinsic properties of their components. This paper deals with the synthesis and characterization of six coordination complexes obtained by the reaction of [MoV2O2 S2 ] 2+ clusters with bis-thiosemicarbazone ligands that contain flexible or rigid spacers between the two thiosemicarbazone units. Interestingly, structural characterization by single-crystal X-ray diffraction, MALDI-TOF MS technique and NMR spectroscopy revealed that the nuclearity of the complex is controlled by the nature of the spacer between the thiosemicarbazone units. Binuclear complexes, namely [MoV2O2 S2 (L 1–3 )], are isolated with flexible spacers while tetranuclear complexes [(MoV2O2 S2 )2 (L 4–6 )2 ] are formed when the bis-thiosemicarbazone ligands are built on rigid spacers.